Peningkatan Pengetahuan Ibu tentang Kehamilan Risiko Tinggi melalui Edukasi Berbasis Komunitas di Dusun Dasan Baru - Putri, Asti Ardiyan; Khairani, Fuji; Wahyuni, Ervin Dini (CV Putra Publisher, 2025)
Pregnancy and childbirth can develop into pathological conditions that pose risks to the health of mothers and fetuses, especially in high-risk pregnancies. The 4T factors in pregnancy (too young, too old, too many children, too close birth spacing) significantly contribute to complications such as bleeding, miscarriage, and fetal death, as well as an increase in maternal mortality rates (MMR). In Indonesia, 34% of pregnant women experience high-risk pregnancies, with MMR reaching 22.4% in 4T pregnancy cases. This study aims to improve pregnant women's knowledge about pregnancy risks through community-based education in Dusun Dasan Baru. A descriptive-analytic quantitative approach was employed, involving 50 pregnant women aged 18–45 years. The education sessions were conducted in three sessions, followed by evaluations using pre-test and post-test questionnaires. Results showed an increase in maternal knowledge from 60% (pre-test) to 87% (post-test).